The Dynamics of Religious Tourism. Case Study: Romania - UNGUREANU, Laura (Journal of Environmental Management and Tourism, 2023)
In recent years, world tourism has diversified its forms of manifestation on an international level, trying to capitalize on the most valuable cultural and religious objectives of a country's cultural and religious heritage. I chose such a theme because we are witnessing a revival of this form of tourism. It is thousands and thousands of years old, and now it is gaining momentum with the help of another vision of religious and pilgrimage tourism. Its new dimensions make it an attractive field for tourism agencies, national and local authorities, tour operators, transport companies, universities, public administrations, those dealing with general and specific infrastructure, as well as others. In Romania, with the collapse of the communist system, the presence of religious topics in the media discourse increased significantly. Particular attention is paid to the phenomenon of pilgrimage, and often this information ends up being the most important news of the day, on many communication channels. Pilgrimages are considered to be important religious events, heavily mediatized and very popular among the faithful, but very little researched. The present work aims to look towards these unexplored areas and study the phenomenon of pilgrimage, to analyze the economic dynamics of the religious phenomenon. Some of these fields are intensively researched abroad, where there is a significant specialized literature, while in Romania, these fields are less investigated. There are many studies in the field, at the international level, but at the national level, the phenomenon is less debated. This is the reason why the proposed case study and the examples used in the paper investigate the Romanian religious realities. In this article we aim to create both an image of religious tourism today and its dynamics in the near future (the evolution of the number of tourists and the economic side of this phenomenon).